Optimizing conservative management on recurrent hypotony maculopathy following glaucoma drainage devices implantation in steroid responder - Yunard, Ardiella; Asrory, Virna Dwi Oktariana; Suryono, Astrianda Nadya; Laksmita, Yulinda Arty; Dzulkarnain, Tiara Azriena (Indian Journal of Case Reports, 2025)
This report describes a case of managing recurrent hypotony maculopathy following glaucoma drainage devices (GDD) implantation with steroids. A 29-year-old female presented with blurred vision and a sudden decrease in visual acuity (VA) and intraocular pressure (IOP) 5 months following the GDD implantation. Assuming hypotony maculopathy as the cause, we started conservative treatment with oral and topical steroids, resulting in functional and structural improvement. However, the same symptoms and findings recurred. The steroid medications were then re-established with tapering down and maintenance of dose, the patient’s IOP and VA remained stable with conservative treatments. The most common cause of hypotony is glaucoma filtering surgery. Conservative management using steroids is frequently effective in treating hypotony maculopathy, especially in steroid responders.